A photocatalytic self-cleaning oil-water separation membrane with pH response characteristics and a preparation method and application thereof
Patent Information
- Application Number
- CN202611155403.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-31
- Publication Date
- 2026-10-20
AI Technical Summary
[0005]针对现有技术中存在的技术问题,本发明提供了一种具有pH响应特性的光催化自清洁油水分离膜及其制备方法和应用,以解决现有PVDF膜极易吸附废水中的油污、有机污染物等杂质,造成膜孔堵塞、膜体污染,进而引发膜通量大幅衰减、油水分离效率下降、使用寿命缩短的技术问题
本发明提供的具有pH响应特性的光催化自清洁油水分离膜的制备方法,通过构建CdS/MIL-125-Br Z型异质结光催化体系,并结合两性离子聚合物与pH响应聚合物协同改性,实现膜材料的超亲水性、优异抗污染性、可逆润湿响应性以及可见光催化自清洁性能;具体而言,通过在PVDF膜基体中引入CdS/MIL-125-Br Z型异质结纳米复合材料,并结合原子转移自由基聚合技术依次接枝两性离子聚合物PSBMA与pH响应性单体,配合非溶剂诱导相分离法实现膜内部结构与表面功能的协同调控,有效解决现有PVDF膜易被油污堵塞、膜通量衰减快、分离效率低、使用寿命短及无法适配不同乳化油乳液分离的缺陷;其中,MIL-125-Br金属有机框架材料具备高比表面积与稳定孔道结构,和CdS纳米颗粒形成的Z型异质结可高效分离光生载流子、抑制电子空穴复合,大幅提升可见光催化活性,能够通过生成活性氧自由基原位降解膜表面有机污染物,赋予膜体优异的光催化自清洁能力,有效改善膜污染问题;膜表面接枝的PSBMA能够形成稳定水合层,显著增强膜的亲水性与抗油污吸附性能,减少油滴沉积堵塞,保障膜通量稳定;同时,接枝的pH响应性单体能够依靠叔胺基团可逆质子化特性,使膜表面润湿性随环境pH动态可调,酸性环境下呈现亲水水下疏油特性、中性及碱性环境下呈现疏水亲油特性,能够适配水包油、油包水不同类型乳化油废水的按需分离,整体大幅提升了乳化油废水的分离效率与处理水质,有效延长膜的使用寿命、提升运行稳定性与经济适用性,显著提升PVDF膜在高浓度乳化油废水处理中规模化应用。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention belongs to the technical field of membrane separation materials and environmental functional materials, and specifically relates to a photocatalytic self-cleaning oil-water separation membrane with pH response characteristics, its preparation method, and its application. Background Technology
[0002] With the rapid development of industrialization, many industrial sectors such as petrochemicals, textile printing and dyeing, and food processing generate a large amount of oily wastewater during production operations, posing a serious threat to the natural ecological environment such as water bodies and soil. Among them, emulsified oily wastewater is much more difficult to treat than ordinary oily wastewater due to the characteristics of small oil droplet size, extremely strong system stability, and inability to naturally stratify. Traditional treatment processes in the industry mainly include gravity sedimentation, air flotation, and chemical flocculation. However, the above-mentioned traditional technologies have limited effectiveness in treating emulsified oily wastewater, making it difficult to achieve complete separation of oil and sludge. The treated wastewater quality cannot meet the current environmental emission standards and industrial reuse requirements.
[0003] Compared to traditional treatment processes, membrane separation technology has gradually become the mainstream technology in the field of oil-water separation due to its outstanding advantages such as high separation efficiency, simple operation, no secondary pollution, green environmental protection, and high degree of automation. It is widely used in the treatment of various oily wastewater. Among them, polyvinylidene fluoride (PVDF) membranes, with their excellent thermal stability, mechanical properties, and chemical corrosion resistance, are suitable for complex industrial wastewater treatment conditions and are one of the most widely used membrane materials in the field of oil-water separation.
[0004] However, existing PVDF membranes have a strong hydrophobic surface. During long-term continuous oil-water separation operation, they are prone to adsorbing impurities such as oil and organic pollutants in wastewater, causing membrane pore blockage and membrane fouling. This leads to a significant decrease in membrane flux, reduced oil-water separation efficiency, and shortened service life, severely reducing the operational stability and economic efficiency of PVDF membranes and greatly limiting their large-scale application in the treatment of high-concentration emulsified oily wastewater. Summary of the Invention
[0005] To address the technical problems existing in the prior art, this invention provides a photocatalytic self-cleaning oil-water separation membrane with pH response characteristics, its preparation method, and its application. This solves the technical problem that existing PVDF membranes easily adsorb impurities such as oil and organic pollutants in wastewater, causing membrane pore blockage and membrane fouling, which in turn leads to a significant decrease in membrane flux, a reduction in oil-water separation efficiency, and a shortened service life.
[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows: This invention provides a method for preparing a photocatalytic self-cleaning oil-water separation membrane with pH-responsive characteristics, comprising: The bromine-functionalized organic ligand Br-BDC was synthesized using 2-aminoterephthalic acid, triethylamine, and α-bromoisobutyryl bromide. MIL-125-Br metal-organic framework material was prepared by reacting the brominated organic ligand Br-BDC with tetrabutyl titanate. CdS nanoparticles were loaded onto the surface of MIL-125-Br metal-organic framework material using a solvothermal method to construct a CdS / MIL-125-Br Z-type heterojunction nanocomposite material. PVDF / CdS / MIL-125-Br composite membranes were prepared by dissolving polyvinylidene fluoride, polyvinylpyrrolidone, and CdS / MIL-125-Br Z-type heterojunction nanocomposite materials in N,N-dimethylacetamide and using a non-solvent-induced phase separation method. Using atom transfer radical polymerization, zwitterionic polymer polysulfobetaine methacrylate was grafted onto the surface of a PVDF / CdS / MIL-125-Br composite membrane to obtain a PVDF / CdS / MIL-125-PSBMA superhydrophilic membrane. Using the ATRP polymerization method, pH-responsive monomers were grafted onto the surface of a PVDF / CdS / MIL-125-PSBMA superhydrophilic membrane to construct a dynamic wetting control layer, thereby obtaining a photocatalytic self-cleaning oil-water separation membrane with pH-responsive characteristics.
[0007] Furthermore, the process of synthesizing the bromine-functionalized organic ligand Br-BDC using 2-aminoterephthalic acid, triethylamine, and α-bromoisobutyryl bromide is as follows: Under nitrogen protection, 2-aminoterephthalic acid and triethylamine were dissolved in tetrahydrofuran and placed in an ice bath. Then, α-bromoisobutyryl bromide was added dropwise. After the addition was complete, the reaction was stirred at room temperature. After the reaction was completed, the by-product salt was removed by centrifugation, and the remaining solution was poured into toluene for precipitation. The precipitated solid was collected and washed with deionized water and acetone in sequence. Then it was dried under vacuum to obtain the bromine-functionalized organic ligand Br-BDC.
[0008] Furthermore, the molar ratio of 2-aminoterephthalic acid, triethylamine and α-bromoisobutyryl bromide is 1:(0.8-1.2):(0.8-1.2).
[0009] Furthermore, the process of preparing MIL-125-Br metal-organic framework material by reacting the brominated organic ligand Br-BDC with tetrabutyl titanate is as follows: Bromine-functionalized organic ligand Br-BDC and tetrabutyl titanate were added to a mixed solvent consisting of N,N-dimethylformamide and methanol. After stirring, a solvothermal reaction was carried out. After the reaction was completed and cooled to room temperature, the precipitate was collected by centrifugation, washed, and dried to obtain the MIL-125-Br metal-organic framework material.
[0010] Furthermore, the process of constructing a CdS / MIL-125-Br Z-type heterojunction nanocomposite material by loading CdS nanoparticles onto the surface of MIL-125-Br metal-organic framework material using a solvothermal method is as follows: MIL-125-Br metal-organic framework material was ultrasonically dispersed in N,N-dimethylformamide, followed by the addition of cadmium nitrate and thiourea and stirring until homogeneous for a solvothermal reaction. After the reaction was completed, the product was collected by filtration, washed, and dried to obtain CdS / MIL-125-Br Z-type heterostructure nanocomposite material.
[0011] Furthermore, the process of preparing a PVDF / CdS / MIL-125-Br composite membrane by dissolving polyvinylidene fluoride, polyvinylpyrrolidone, and CdS / MIL-125-Br Z-type heterojunction nanocomposite material in N,N-dimethylacetamide and using a solvent-inducing phase separation method is as follows: Polyvinylidene fluoride (PVDF) and polyvinylpyrrolidone (PVP) were added to N,N-dimethylacetamide and heated and stirred until completely dissolved to obtain a homogeneous and transparent PVDF mixed solution. CdS / MIL-125-Br Z-type heterojunction nanocomposite material was ultrasonically dispersed in N,N-dimethylacetamide to obtain a CdS / MIL-125-Br nanocomposite solution. The PVDF mixed solution and the CdS / MIL-125-Br nanocomposite solution were mixed and heated and stirred to obtain a uniform casting solution. After degassing, the casting solution was uniformly coated onto the surface of a glass plate, exposed to air, and then immersed in a coagulation bath for phase inversion to obtain a PVDF / CdS / MIL-125-Br composite membrane.
[0012] Furthermore, the process of grafting the zwitterionic polymer polysulfobetaine methacrylate onto the surface of the PVDF / CdS / MIL-125-Br composite membrane using atom transfer radical polymerization to obtain the PVDF / CdS / MIL-125-PSBMA superhydrophilic membrane is as follows: The PVDF / CdS / MIL-125-Br composite membrane was immersed in a mixed solution of methanol and deionized water, and SBMA monomer, 2,2-bipyridine and CuBr were added. The ATRP polymerization reaction was carried out under nitrogen protection. After the reaction was completed, the membrane was washed and dried to obtain the PVDF / CdS / MIL-125-PSBMA superhydrophilic membrane.
[0013] Furthermore, using the ATRP polymerization method, pH-responsive monomers were grafted onto the surface of the PVDF / CdS / MIL-125-PSBMA superhydrophilic membrane to construct a dynamically wetting control layer, thus obtaining a photocatalytic self-cleaning oil-water separation membrane with pH-responsive characteristics, as follows: The PVDF / CdS / MIL-125-PSBMA superhydrophilic membrane was immersed in a mixed solution of methanol and deionized water, and DMAEMA monomer, Bpy and CuBr were added. The ATRP polymerization reaction was carried out under nitrogen protection. After the reaction, the membrane was washed and dried to obtain a photocatalytic self-cleaning oil-water separation membrane with pH response characteristics.
[0014] The present invention also provides a photocatalytic self-cleaning oil-water separation membrane with pH response characteristics, which is prepared by the aforementioned method for preparing a photocatalytic self-cleaning oil-water separation membrane with pH response characteristics; Among them, under acidic conditions, the photocatalytic self-cleaning oil-water separation membrane with pH response characteristics exhibits superhydrophilic / underwater superoleophobic properties. Under neutral or alkaline conditions, the photocatalytic self-cleaning oil-water separation membrane with pH response characteristics exhibits hydrophobic / oleophilic properties. Under the synergistic effect of visible light and H2O2, the photocatalytic self-cleaning oil-water separation membrane with pH response characteristics can degrade methylene blue, thereby achieving photocatalytic self-cleaning of the membrane material.
[0015] The present invention also provides an application of a photocatalytic self-cleaning oil-water separation membrane with pH response characteristics, wherein the photocatalytic self-cleaning oil-water separation membrane with pH response characteristics is used for oil-water separation treatment of emulsified oily wastewater, complex oil-water systems or industrial oily waste liquid.
[0016] Compared with the prior art, the beneficial effects of the present invention are as follows: The present invention provides a method for preparing a photocatalytic self-cleaning oil-water separation membrane with pH-responsive characteristics. This method constructs a CdS / MIL-125-Br Z-type heterojunction photocatalytic system and combines it with zwitterionic polymers and pH-responsive polymers for synergistic modification, achieving superhydrophilicity, excellent antifouling properties, reversible wetting response, and visible light photocatalytic self-cleaning performance of the membrane material. Specifically, this is achieved by introducing CdS / MIL-125-Br into a PVDF membrane substrate. Z-shaped heterojunction nanocomposites, combined with atom transfer radical polymerization (ATRP) to sequentially graft zwitterionic polymer PSBMA and pH-responsive monomers, along with a solvent-inducible phase separation method, achieve synergistic regulation of the membrane's internal structure and surface function. This effectively addresses the shortcomings of existing PVDF membranes, such as easy clogging by oil contaminants, rapid flux decay, low separation efficiency, short service life, and inability to adapt to the separation of different emulsion oils. Among these, the MIL-125-Br metal-organic framework material possesses a high specific surface area and stable pore structure. The Z-shaped heterojunction formed with CdS nanoparticles can efficiently separate photogenerated carriers and suppress electron-hole recombination, significantly enhancing visible light photocatalytic activity. It can also degrade organic pollutants on the membrane surface in situ by generating reactive oxygen species, endowing the membrane with excellent photocatalytic properties. The self-cleaning capability effectively improves membrane fouling issues. The PSBMA grafted onto the membrane surface forms a stable hydration layer, significantly enhancing the membrane's hydrophilicity and anti-oil adsorption performance, reducing oil droplet deposition and clogging, and ensuring stable membrane flux. Simultaneously, the grafted pH-responsive monomers, relying on the reversible protonation properties of tertiary amine groups, allow the membrane surface wettability to be dynamically adjusted according to the ambient pH. It exhibits hydrophilic underwater oleophobic properties in acidic environments and hydrophobic oleophilic properties in neutral and alkaline environments. This enables the on-demand separation of different types of emulsified oily wastewater, such as oil-in-water and water-in-oil emulsions, significantly improving the overall separation efficiency and treated water quality of emulsified oily wastewater. This effectively extends membrane lifespan, enhances operational stability and economic applicability, and significantly promotes the large-scale application of PVDF membranes in the treatment of high-concentration emulsified oily wastewater.
[0017] The photocatalytic self-cleaning oil-water separation membrane with pH response characteristics and its application provided by this invention possess all the advantages of the aforementioned preparation method of the photocatalytic self-cleaning oil-water separation membrane with pH response characteristics. Attached Figure Description
[0018] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0019] Figure 1This is a schematic diagram of the photocatalytic self-cleaning mechanism of the photocatalytic self-cleaning oil-water separation membrane with pH response characteristics prepared in this invention. Figure 2 SEM images of MIL-125-Br(a1-a2) and CdS / MIL-125-Br(b1-b2) nanomaterials in Example 1; Figure 3 The images show surface and cross-sectional SEM images of the original PVDF membrane (a1-a4), PVDF / CdS / MIL-125-Br membrane (b1-b4), PVDF / CdS / MIL-125-PSBMA membrane (c1-c4), and PVDF / CdS / MIL-125-PSADA membrane (d1-d4) in Example 1. Figure 4 AFM images and surface roughness analysis diagrams of the PVDF film (a), PVDF / CdS / MIL-125-Br film (b), PVDF / CdS / MIL-125-PSBMA film (c), and PVDF / CdS / MIL-125-PSADA film (d) in Example 1 are shown. Figure 5 XRD patterns of MIL-125-Br and CdS / MIL-125-Br (a) and ATR-FTIR spectra of MIL-125-Br, CdS / MIL-125-Br, PVDF / CdS / MIL-125-Br, PVDF / CdS / MIL-125-PSBMA membrane and PVDF / CdS / MIL-125-PSADA membrane (b) are shown in Example 1. Figure 6 The WCA(a) of the photocatalytic self-cleaning oil-water separation membrane with pH response characteristics prepared in Examples 1-4, and the UWOCA of 1,2-dichloroethane, n-hexane, toluene, and petroleum ether on the PVDF / CdS / MIL-125-PSBMA membrane in Example 1; Figure 7 The graph shows the effect of different CdS / MIL-125-Br addition amounts on the membrane pure water flux (a) and separation efficiency (b) in Example 1, as well as the separation flux and separation efficiency of the PVDF / CdS / MIL-125-PSBMA membrane for different oil-in-water emulsions (c) and (d). Figure 8Microscopic images of the emulsions before separation of PVDF / CdS / MIL-125-PSBMA membranes for 1,2-petroleum ether / water emulsion (a), n-hexane / water emulsion (b), 1,2-dichloroethane / water emulsion (c), and toluene / water emulsion (d) in Example 1, and the filtrate after separation by the PVDF / CdS / MIL-125-PSBMA membrane; Figure 9 This is a DLS curve of the PVDF / CdS / MIL-125-PSADA oil-water separation membrane in Example 1 before and after emulsion separation; Figure 9 In the diagram, a1 is the DLS curve of petroleum ether bulk solution; a2 is the DLS curve of petroleum ether filtrate; b1 is the DLS curve of n-hexane emulsion; b2 is the DLS curve of n-hexane filtrate; c1 is the DLS curve of 1,2-dichloroethane bulk emulsion; c2 is the DLS curve of 1,2-dichloroethane bulk filtrate; d1 is the DLS curve of toluene emulsion; d2 is the DLS curve of toluene filtrate. Figure 10 The flux and separation efficiency of the PVDF / CdS / MIL-125-PSBMA membrane for the water-in-hexane emulsion during 5 cycles in Example 1, and the flux and separation efficiency of the hexane-in-water emulsion during 5 cycles (b), the Frr, Rt, Rr and Rir of the PVDF / CdS / MIL-125-PSBMA membrane during 5 cycles (c), and the changes in reversible cyclic wettability of the PVDF / CdS / MIL-125-PSA membrane under different pH conditions (d) are shown. Figure 11 The images show the photocatalytic degradation of MB in different reaction systems by the PVDF / CdS / MIL-125-PSBMA membrane in Example 1 (a) and the UV-vis absorption spectra of MB aqueous solution after exposure for different times (b). Detailed Implementation
[0020] To make the technical problems, technical solutions, and beneficial effects solved by this application clearer, the technical solutions in the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of this application, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of this application without creative effort are within the scope of protection of this application.
[0021] This invention provides a method for preparing a photocatalytic self-cleaning membrane with pH-responsive characteristics, comprising the following steps: Step 1: Prepare MIL-125-Br material with ATRP initiation sites and construct CdS / MIL-125-Br Z-type heterojunction nanocomposite material.
[0022] Specifically, the implementation process is as follows: Under nitrogen protection, 2-aminoterephthalic acid and triethylamine were dissolved in anhydrous THF and cooled in an ice bath. Then, α-bromoisobutyryl bromide was added dropwise. After the addition was complete, the mixture was stirred overnight at room temperature. After the reaction was completed, the salt byproducts were removed by centrifugation, and the resulting solution was poured into toluene to precipitate. The precipitate was collected and washed successively with deionized water and acetone, and dried under vacuum to obtain the bromine-functionalized organic ligand Br-BDC.
[0023] Bromine-functionalized organic ligand Br-BDC and tetrabutyl titanate were added to a mixed solvent of DMF and methanol and stirred vigorously to form a homogeneous solution. The resulting homogeneous solution was then transferred to a polytetrafluoroethylene-lined high-pressure reactor for a solvothermal reaction. After the reaction was completed and cooled to room temperature, the precipitate was collected by centrifugation and repeatedly washed with DMF and methanol, respectively, and then vacuum dried to obtain MIL-125-Br metal-organic framework material.
[0024] MIL-125-Br metal-organic framework material was ultrasonically dispersed in DMF; then cadmium nitrate and thiourea were added, and stirring was continued to form a homogeneous suspension; the resulting homogeneous suspension was transferred to a polytetrafluoroethylene-lined autoclave for reaction; after cooling, the product was collected by filtration, and repeatedly washed with DMF and methanol, and dried to obtain CdS / MIL-125-Br Z-type heterojunction nanocomposite material.
[0025] Step 2: Using the non-solvent induced phase separation method (NIPS), the CdS / MIL-125-Br Z-type heterojunction nanocomposite material was blended into the PVDF casting solution to prepare the PVDF / CdS / MIL-125-Br membrane.
[0026] Specifically, the implementation process is as follows: PVDF and PVP were added to DMAc and heated and stirred until completely dissolved to form a homogeneous and transparent solution. Simultaneously, CdS / MIL-125-Br Z-type heterojunction nanocomposite material was ultrasonically dispersed in DMAc to form a stable dispersion. The homogeneous and transparent solution and the stable dispersion were then mixed and heated and stirred to obtain a uniform casting solution. After the uniform casting solution was allowed to stand to remove bubbles, it was uniformly coated onto the surface of a glass plate and briefly exposed to air before being rapidly transferred to a pure water coagulation bath for phase inversion to obtain a PVDF / CdS / MIL-125-Br composite membrane. The prepared PVDF / CdS / MIL-125-Br composite membrane was soaked in deionized water to remove residual solvent and then stored for later use.
[0027] Step 3: Using atom transfer radical polymerization (ATRP), the zwitterionic polymer polysulfobetaine methacrylate (PSBMA) is grafted onto the surface of the PVDF / CdS / MIL-125-Br composite membrane to obtain a PVDF / CdS / MIL-125-PSBMA superhydrophilic membrane with superhydrophilic and antifouling properties.
[0028] Specifically, the implementation process is as follows: The PVDF / CdS / MIL-125-Br composite membrane was immersed in a mixed solution of methanol and deionized water, and SBMA monomer was added to it. Subsequently, 2,2-bipyridine and CuBr catalytic system were added, and the reaction was carried out at 60°C under nitrogen protection. After the reaction was completed, the membrane was washed with ethanol and deionized water in sequence, and dried at room temperature to obtain the PVDF / CdS / MIL-125-PSBMA superhydrophilic membrane.
[0029] Step 4: Utilizing the biocompatibility of ATRP polymerization, pH-responsive monomers are further grafted onto the surface of the PVDF / CdS / MIL-125-PSBMA superhydrophilic membrane to obtain a PVDF / CdS / MIL-125-PSADA on-demand oil-water separation membrane with both pH responsiveness and photocatalytic self-cleaning properties, serving as a photocatalytic self-cleaning oil-water separation membrane with pH responsive characteristics; wherein, the pH-responsive monomer is 2-(dimethylamino)ethyl methacrylate (DMAEMA).
[0030] Specifically, the implementation process is as follows: The PVDF / CdS / MIL-125-PSBMA superhydrophilic membrane was immersed in a mixed solution of methanol and deionized water, and DMAEMA was added as a pH-responsive monomer. Subsequently, 2,2-bipyridine and CuBr were added as a catalytic system, and the polymerization reaction was carried out under nitrogen protection. After the reaction was completed, the membrane was washed with ethanol and deionized water and dried at room temperature to obtain a photocatalytic self-cleaning oil-water separation membrane with pH-responsive characteristics.
[0031] Preparation principle: The method for preparing a photocatalytic self-cleaning oil-water separation membrane with pH-responsive properties according to the present invention uses polyvinylidene fluoride (PVDF) as the matrix material. By introducing a CdS / MIL-125-Br Z-type heterojunction nanocomposite material with visible light responsiveness, and combining it with atom transfer radical polymerization (ATRP) technology, zwitterionic polymer polysulfobetaine methacrylate (PSBMA) and pH-responsive monomer 2-(dimethylamino)ethyl methacrylate (DMAEMA) are grafted onto the membrane surface, thereby constructing a functional membrane with efficient oil-water separation, anti-fouling, self-cleaning and pH-responsive properties.
[0032] Among them, MIL-125-Br metal-organic framework, as a titanium-based metal-organic framework material, has a high specific surface area, abundant pore structure, and good chemical stability. By combining with CdS to form a Z-shaped heterojunction structure, it can effectively promote the separation of photogenerated electrons and holes, inhibit electron-hole recombination, and improve photocatalytic activity. Under visible light irradiation, the CdS / MIL-125-Br heterojunction can generate a large number of reactive oxygen species (·OH, ·O2). - This enables in-situ degradation of organic pollutants on the membrane surface, giving the membrane excellent photocatalytic self-cleaning properties.
[0033] Secondly, by grafting PSBMA zwitterionic polymer onto the membrane surface via ATRP polymerization, utilizing the simultaneous presence of cationic and anionic groups in its molecules, a stable hydration layer is formed on the membrane surface, significantly improving the membrane's hydrophilicity and antifouling performance, and reducing oil droplet adsorption and deposition on the membrane surface. Furthermore, after further grafting DMAEMA monomer, the reversible protonation property of the tertiary amine groups in DMAEMA allows the membrane surface wettability to change with environmental pH. Specifically, under acidic conditions, DMAEMA segments protonate and extend, resulting in a hydrophilic / underwater oleophobic membrane surface; while under neutral or alkaline conditions, DMAEMA segments deprotonate and shrink, transforming the membrane surface into a hydrophobic / oleophilic membrane surface. Therefore, this pH-responsive photocatalytic self-cleaning oil-water separation membrane can achieve on-demand separation of different types of emulsions (oil-in-water or water-in-oil emulsions).
[0034] In this invention, a non-solvent induced phase separation (NIPS) method is used to prepare the membrane substrate, so that CdS / MIL-125-Br nanomaterials are uniformly dispersed inside the PVDF membrane. Combined with surface ATRP grafting modification technology, the synergistic regulation of the internal structure and surface function of the membrane is achieved, thereby obtaining an on-demand oil-water separation membrane with high separation efficiency, excellent anti-fouling ability, good cycle stability and photocatalytic self-cleaning function.
[0035] It should be noted that the zwitterionic polymer PSBMA, due to the simultaneous presence of positive and negative charged groups, can form a stable hydration layer through electrostatic interactions, thereby effectively reducing oil adsorption and improving antifouling performance. Furthermore, photocatalysis can generate highly reactive oxygen species with strong oxidizing capabilities under light irradiation, enabling in-situ degradation of organic pollutants and thus endowing the membrane material with self-cleaning properties. The metal-organic framework material MIL-125(Ti) possesses a high specific surface area and excellent photoresponse capability, but suffers from rapid photogenerated electron-hole recombination. Introducing CdS to construct a CdS / MIL-125-Br Z-type heterojunction can effectively promote carrier separation and improve visible light photocatalytic activity. On the other hand, DMAEMA, as a typical pH-responsive monomer, can reversibly regulate its molecular chain conformation with pH changes, thereby achieving dynamic switching of membrane surface wettability.
[0036] Explanation of the photocatalytic self-cleaning mechanism: As attached Figure 1 As shown, attached Figure 1 The photocatalytic self-cleaning mechanism of the photocatalytic self-cleaning membrane with pH response characteristics described in this invention is given in detail below: The photocatalytic self-cleaning membrane with pH-responsive properties prepared in this invention internally supports a CdS / MIL-125-Br Z-type heterojunction nanocomposite material. Under visible light irradiation, CdS and MIL-125-Br are photoexcited to generate photogenerated electrons and holes. The Z-type heterojunction structure can effectively promote the separation of photogenerated carriers and suppress electron-hole recombination. Photogenerated electrons gathered in the LUMO orbital reduce oxygen in the system to generate superoxide radicals. Photogenerated holes enriched at the valence band oxidize water molecules to generate hydroxyl radicals and simultaneously produce hydrogen peroxide, ·OH, and ·O2. - Two types of highly oxidizing reactive oxygen species can oxidize and decompose organic pollutants such as oil and methylene blue adsorbed on the membrane surface into small molecule byproducts. Combined with the stable hydration layer formed by zwitterionic PSBMA on the membrane surface, water flow can easily wash away the pollutant residues after degradation. Furthermore, the degradation effect is further enhanced under the synergistic effect of visible light and H2O2, realizing in-situ degradation of pollutants on the membrane surface and restoration of membrane flux, thus endowing the composite membrane with stable visible light photocatalytic self-cleaning performance.
[0037] The following specific embodiments further explain the preparation method of the photocatalytic self-cleaning membrane with pH response characteristics provided by the present invention: Example 1 This embodiment 1 provides a method for preparing a photocatalytic self-cleaning oil-water separation membrane with pH-responsive characteristics, comprising the following steps: Step 1: Under nitrogen protection, 4.67 g of 2-aminoterephthalic acid and 2.59 g of triethylamine were added to 50 mL of anhydrous THF and stirred in an ice bath until completely dissolved. Then, 5.92 g of α-bromoisobutyryl bromide was slowly added dropwise over 30 min. After the addition was complete, the reaction was continued at room temperature with stirring for 12 h. After the reaction was complete, the generated salt byproducts were removed by centrifugation, and the resulting supernatant was poured into toluene to precipitate. The obtained solid product was collected and washed three times successively with deionized water and acetone, and finally dried under vacuum at room temperature for 12 h to obtain a pale yellow Br-BDC powder. Then, 0.56 g of Br-BDC and 0.6 mL of tetrabutyl titanate were weighed and added to a mixed solution of 40 mL of LDM and MeOH (volume ratio 9:1), and stirred vigorously at room temperature for 30 min to form a homogeneous precursor solution. The resulting solution was then transferred to a 100 mL polytetrafluoroethylene-lined high-pressure reactor and subjected to a solvothermal reaction at 150 °C for 24 h. After the reaction was complete and the mixture cooled naturally to room temperature, the yellow-brown precipitate was collected by centrifugation and washed three times with DMF and methanol, respectively. Finally, it was vacuum dried at 60 °C for 12 h to obtain MIL-125-Br powder. A certain amount of MIL-125-Br powder was then weighed and added to 70 mL of DMF, and ultrasonically dispersed for 30 min. Subsequently, 0.21 g of cadmium nitrate and 0.05 g of thiourea were added, and the mixture was magnetically stirred for 30 min to form a homogeneous suspension. The resulting suspension was transferred to a 100 mL polytetrafluoroethylene-lined high-pressure reactor and reacted at 200 °C for 2 h. After the reaction was complete and the mixture cooled to room temperature, the product was collected by filtration and washed three times with DMF and methanol, respectively, to remove residual ions and unreacted substances. Finally, it was vacuum dried at 60 °C for 12 h to obtain the CdS / MIL-125-Br nanocomposite material.
[0038] Step 2: Add 0.4g PVDF and 0.15g PVP to 2.7mL DMAc and heat and stir at 60℃ for 2h to obtain a homogeneous and transparent PVDF solution. Simultaneously, add 0.08g CdS / MIL-125-Br nanocomposite material to 2mL DMAc and ultrasonically disperse for 30min to obtain a homogeneous dispersion. Then mix the two solutions and continue stirring at 60℃ for 10h to form a homogeneous casting solution. After allowing the resulting casting solution to stand to remove bubbles, pour it evenly onto a clean glass plate and use a 300μm doctor blade to coat the membrane. After coating, briefly expose the membrane to air for 30s, then quickly immerse it in a 40℃ pure water coagulation bath for phase inversion. Soak the resulting membrane material in deionized water at room temperature for 24h to remove residual solvent, and finally store it in deionized water for later use, designated as the PVDF / CdS / MIL-125-Br membrane.
[0039] Step 3: Immerse the PVDF / CdS / MIL-125-Br membrane in a mixed solution of methanol and deionized water (volume ratio 1:1). Then, add 1.2 g of SBMA monomer to the system and deoxygenate under nitrogen for 30 min. Next, add 133.6 mg of 2,2-bipyridine (Bpy) and 50 mg of CuBr catalyst, and react at 60 °C for 24 h under nitrogen protection. After the reaction, wash the resulting membrane three times with ethanol and deionized water to remove unreacted monomer and residual catalyst. Finally, dry at room temperature for 24 h to obtain the PVDF / CdS / MIL-125-PSBMA membrane.
[0040] Step 4: Immerse the PVDF / CdS / MIL-125-PSBMA membrane in a mixed solution of methanol and deionized water (volume ratio 1:1). Then add 6 mL of DMAEMA monomer and 112.5 mg of Bpy, and deoxygenate the system under nitrogen for 30 min. Next, add 34.4 mg of CuBr catalyst and react at 60 °C for 24 h under nitrogen protection. After the reaction, wash the resulting membrane three times with ethanol and deionized water to remove unreacted monomer and residual catalyst. Finally, dry at room temperature for 24 h to obtain a photocatalytic self-cleaning oil-water separation membrane with pH-responsive characteristics, denoted as PVDF / CdS / MIL-125-PSADA on-demand oil-water separation membrane (M1).
[0041] Example 2 Example 2 is basically the same as Example 1; the difference is that the amount of CdS / MIL-125-Br nanoparticles added in step 4 is 0.03g, and the other conditions remain unchanged. Finally, a photocatalytic self-cleaning oil-water separation membrane with pH response characteristics is obtained, which is denoted as PVDF / CdS / MIL-125-PSADA-2 on-demand oil-water separation membrane (abbreviated as M2).
[0042] Example 3 Example 3 is basically the same as Example 1, except that: in step 4, the amount of CdS / MIL-125-Br nanoparticles added is 0.06g, and the other conditions remain unchanged. Finally, a photocatalytic self-cleaning oil-water separation membrane with pH response characteristics is obtained, which is denoted as PVDF / CdS / MIL-125-PSADA-3 on-demand oil-water separation membrane (abbreviated as M3).
[0043] Example 4 Example 4 is basically the same as Example 1, except that: in step 4, the amount of CdS / MIL-125-Br nanoparticles added is 0.12g, and the other conditions remain unchanged. Finally, a photocatalytic self-cleaning oil-water separation membrane with pH response characteristics is obtained, which is denoted as PVDF / CdS / MIL-125-PSADA-4 on-demand oil-water separation membrane (abbreviated as M4).
[0044] Performance test results analysis and explanation: As attached Figure 2 As shown, attached Figure 2 Electron microscopy (SEM) images of MIL-125-Br (a1-a2) and CdS / MIL-125-Br (b1-b2) in Example 1 are provided; see attached... Figure 2 As can be seen, MIL-125-Br exhibits a regular and ordered sheet-like structure with a relatively flat and uniformly dispersed surface. After being loaded with CdS via a hydrothermal reaction, CdS nanoparticles are randomly distributed on the surface of MIL-125-Br, forming a tightly contacted CdS / MIL-125-Br Z-type heterojunction structure. The construction of this heterojunction facilitates the rapid separation and migration of photogenerated electrons and holes, thereby improving the visible light photocatalytic activity of the material.
[0045] As attached Figure 3 As shown, attached Figure 3 SEM images of the surface and cross-sectional morphology of the PVDF / CdS / MIL-125-PSBMA films (a1-a2), PVDF / CdS / MIL-125-PSBMA (b1-b2), and PVDF / CdS / MIL-125-PSADA (c1-c2) in Example 1 are provided; from the attached... Figure 3 As can be seen, the PVDF / CdS / MIL-125-Br membrane surface exhibits a uniformly distributed nanoscale protrusion structure with a uniform pore size distribution. After PSBMA grafting, a continuous and dense hydrophilic layer is formed on the membrane surface. Further grafting of DMAEMA results in the membrane surface being uniformly covered by a polymer brush layer, further reducing the pore size. Each membrane cross-section maintains a typical asymmetric finger-like pore structure, indicating that the surface modification process did not damage the internal structure of the membrane.
[0046] As attached Figure 4 As shown, attached Figure 4 AFM images of the surface morphology of PVDF film (a), PVDF / CdS / MIL-125-Br film (b), PVDF / CdS / MIL-125-PSBMA and PVDF / CdS / MIL-125-PSADA (d) in Example 1 are provided; from the attached... Figure 4As can be seen, the surface roughness Ra of the original PVDF membrane was 6.18 nm. After introducing CdS / MIL-125-Br, the roughness increased to 7.31 nm, which is due to the formation of micro- and nano-scale protrusions on the membrane surface by nanoparticles. After grafting PSBMA, the polymer brush filled some surface defects, reducing the roughness to 6.03 nm. After further grafting DMAEMA, the roughness was further reduced to 4.78 nm. Appropriate control of surface roughness is beneficial to enhancing the wettability and antifouling properties of the membrane surface.
[0047] As attached Figure 5 As shown, attached Figure 5 The XRD patterns of MIL-125-Br and MIL-125 / CdS in Example 1 are given, as well as the ATR-FTIR spectra (b) of the MIL-125-Br, CdS / MIL-125-Br, PVDF / CdS / MIL-125-Br, PVDF / CdS / MIL-125-PSBMA-3 and PVDF / CdS / MIL-125-PSADA films; see attached. Figure 5 As shown in (a), MIL-125-Br exhibits distinct characteristic diffraction peaks, indicating the successful formation of its crystal structure. After loading CdS, the CdS / MIL-125-Br sample retains the characteristic diffraction peaks of MIL-125-Br while also displaying the characteristic peaks corresponding to CdS, indicating that CdS has been successfully loaded onto the surface of MIL-125-Br, forming a CdS / MIL-125-Br composite structure. (See attached image) Figure 5 As shown in (b), MIL-125-Br exhibits typical skeletal structure characteristic absorption peaks. After loading CdS, Cd-S related characteristic absorption peaks appear, indicating successful CdS introduction. After incorporating CdS / MIL-125-Br into the PVDF membrane, the characteristic absorption peaks of both PVDF and CdS / MIL-125-Br are retained in the membrane. Further grafting of PSBMA and PDMAEMA results in corresponding functional group characteristic absorption peaks, indicating that both polymer brush layers have been successfully grafted onto the membrane surface. Combined XRD and ATR-FTIR analysis results show that the CdS / MIL-125-Br composite material was successfully prepared and successfully introduced into the PVDF membrane matrix; simultaneously, PSBMA and PDMAEMA were successfully grafted onto the membrane surface, proving the successful construction of the PVDF / CdS / MIL-125-PSADA composite membrane prepared in this invention.
[0048] As attached Figure 6 As shown, attached Figure 6The WCA (a) of PVDF / CdS / MIL-125-PSBMA membranes with different CdS / MIL-125-Br contents prepared in Examples 1-4 and the UWOCA (b) of 1,2-dichloroethane, n-hexane, toluene, and petroleum ether on the PVDF / CdS / MIL-125-PSBMA-3 membrane in Example 1 are given; from Figure 6 As shown in (a), the water contact angle of the membrane surface gradually decreases with increasing CdS / MIL-125-Br addition. After grafting zwitterions, the water contact angle further decreases, with the PVDF / CdS / MIL-125-PSBMA-3 membrane exhibiting the best wetting performance; its water contact angle rapidly drops to 0° within approximately 3 seconds, demonstrating superhydrophilic properties. Simultaneously, it exhibits excellent underwater superoleophobic properties against oil phases such as n-hexane, petroleum ether, toluene, and 1,2-dichloroethane. Figure 6 As shown in (b), the underwater oil contact angle is greater than 140°. This indicates that the synergistic effect of the zwitterionic polymer and CdS / MIL-125-Br significantly improves the hydrophilicity and oil fouling resistance of the membrane surface.
[0049] As attached Figure 7 As shown, attached Figure 7 The following data are presented: water flux (a) of membranes with different MOF contents prepared in Examples 1-4 before and after grafting zwitterions; flux and separation efficiency (b) of membranes with different MOF contents for n-hexane-in-water emulsions; separation flux and separation efficiency (c) of PVDF / CdS / MIL-125-PSBMA membrane in Example 1 for different oil-in-water emulsions; and separation flux and separation efficiency (d) of PVDF / CdS / MIL-125-PSADA membrane for different oil-in-water emulsions.
[0050] From the appendix Figure 7As can be seen, with the increase of CdS / MIL-125-Br addition, the pure water flux of the membrane first increases and then decreases. When the CdS / MIL-125-Br addition reaches an appropriate value, the membrane exhibits a high pure water flux; after further increasing the addition, the membrane flux decreases due to the impact on some pores. After PSBMA grafting modification, the membrane still maintains high flux performance and good separation performance. Further separation tests were conducted on different oil-in-water emulsions. The results showed that the PVDF / CdS / MIL-125-PSBMA membrane exhibited high separation flux and efficiency for n-hexane emulsions. Considering the membrane's wettability, separation flux, and separation efficiency, the PVDF / CdS / MIL-125-PSBMA membrane was selected as the subject of subsequent research. The PVDF / CdS / MIL-125-PSADA membrane obtained after further modification with PDMAEMA showed excellent separation performance for various oil-in-water emulsions such as petroleum ether, n-hexane, toluene, and 1,2-dichloroethane, with separation efficiencies all above 95%, while also possessing high separation flux. The test results indicate that the composite membrane prepared in this invention has excellent emulsion separation performance and good applicability, and can meet the high-efficiency treatment requirements of different types of oily wastewater.
[0051] As attached Figure 8 As shown, attached Figure 8 Microscopic images of PVDF / CdS / MIL-125-PSBMA before and after separation of 1,2-petroleum ether / water emulsion (a), n-hexane / water emulsion (b), 1,2-dichloroethane / water emulsion (c), and toluene / water emulsion (d) in Example 1 are provided; see attached... Figure 8 As can be seen, before separation, all emulsions were milky white and turbid, indicating that the oil phase was uniformly dispersed in the continuous aqueous phase in the form of tiny droplets, forming a stable oil-in-water emulsion system. Under a microscope, a large number of small and densely distributed oil droplets could be observed. After separation by the PVDF / CdS / MIL-125-PSADA membrane, the filtrates of each emulsion changed from a milky white and turbid state to a clear and transparent state, indicating that the oil droplets in the emulsion were effectively retained. In the corresponding microscopic images, no obvious oil droplets were observed in the filtrate, indicating that the membrane can effectively block the dispersed oil droplets in the emulsion from passing through the membrane pores, achieving efficient separation of the oil and water phases. The above results show that the PVDF / CdS / MIL-125-PSADA membrane prepared in this invention has excellent separation performance for different types of oil-in-water emulsions such as petroleum ether, n-hexane, 1,2-dichloroethane, and toluene, and can achieve efficient demulsification and oil droplet retention in the emulsion system.
[0052] As attached Figure 9 As shown, attached Figure 9DLS curves of the PVDF / CdS / MIL-125-PSADA membrane before and after separation of petroleum ether / water emulsions (a1-a2), n-hexane / water emulsions (b1-b2), 1,2-dichloroethane / water emulsions (c1-c2), and toluene / water emulsions (d1-d2) in Example 1 are provided. (See attached...) Figure 9 As can be seen, before separation, the droplet size distribution range in each emulsion was relatively wide, mainly concentrated between 500-3500 nm, indicating the presence of a large number of nano- and micron-sized oil droplets in the emulsion. After separation by PVDF / CdS / MIL-125-PSADA membrane, the particle size distribution range in the filtrate was significantly reduced, large oil droplets basically disappeared, and only a small number of smaller particles remained. Compared with the original emulsion, the number of droplets in the filtrate was significantly reduced, and the particle size distribution was significantly narrowed.
[0053] As attached Figure 10 As shown, attached Figure 10 The flux and separation efficiency (a) of the PVDF / CdS / MIL-125-PSADA membrane for the water-in-hexane emulsion in Example 1 after 5 cycles are given, as well as the F in multiple cycles of the PVDF / CdS / MIL-125-PSADA membrane. rr R t R r and R ir (b) Flux and separation efficiency of the PVDF / CdS / MIL-125-PSADA membrane for n-hexane-in-water emulsions during 5 cycles; (c) Changes in reversible cyclic wettability of the PVDF / CdS / MIL-125-PSADA membrane under different pH conditions; (d) From the appendix... Figure 10 As can be seen, after five consecutive cycles of separation, the membrane maintained high separation efficiency for both oil-in-water and water-in-oil emulsions, with only a slight decrease in separation flux, indicating good cyclic stability. Simultaneously, the membrane flux recovery rate remained consistently high, and the irreversible fouling rate remained low, demonstrating excellent antifouling and reusability. Further testing of the membrane's wettability under different pH conditions revealed that the membrane surface contact angle significantly decreased after acidic treatment, but recovered to a high level after alkaline treatment. After multiple cycles, the membrane maintained a stable wettability transition capability, indicating that PDMAEMA imparts excellent pH response performance to the membrane, achieving reversible control of membrane surface wettability.
[0054] As attached Figure 11 As shown, attached Figure 11 The photocatalytic degradation of MB in different reaction systems by the PVDF / CdS / MIL-125-PSADA-3 membrane in Example 1 is shown in (a), and the UV-vis absorption spectra of MB aqueous solution after exposure for different times are shown in (b). (See attached...) Figure 11 As can be seen, under visible light irradiation, the PVDF / CdS / MIL-125-PSADA-3 membrane exhibits higher methylene blue degradation efficiency compared to the H2O2 system alone and the membrane without CdS loading. Furthermore, the methylene blue degradation efficiency is further improved under the synergistic effect of H2O2, indicating that the CdS / MIL-125-Br composite structure can effectively enhance the photocatalytic activity of the membrane. Simultaneously, the UV-Vis absorption spectrum intensity of the methylene blue solution gradually decreases with increasing reaction time until it almost disappears, indicating that the methylene blue is continuously degraded. The test results demonstrate that the composite membrane prepared in this invention possesses excellent photocatalytic degradation performance and self-cleaning ability, effectively removing organic pollutants from the membrane surface and water.
[0055] The method for preparing a photocatalytic self-cleaning oil-water separation membrane with pH-responsive characteristics according to the present invention involves preparing a CdS / MIL-125-Br photocatalytic composite material by hydrothermal method and uniformly introducing it into a PVDF membrane substrate to construct a composite membrane substrate with both photocatalytic activity and surface initiation function. Based on this, the zwitterionic polymer PSBMA and the pH-responsive polymer PDMAEMA are sequentially grafted by surface-initiated ATRP polymerization, and a composite membrane material with pH-responsive wettability regulation, oil-water emulsion separation, anti-fouling and photocatalytic self-cleaning functions is successfully prepared.
[0056] In this invention, the introduction of the CdS / MIL-125-Br composite material not only improves the hydrophilicity of the membrane surface but also constructs a highly efficient CdS / MIL-125-Br heterojunction structure, which facilitates the separation of photogenerated electrons and holes and improves the generation efficiency of reactive oxygen species, thereby endowing the membrane with excellent photocatalytic performance. The PSBMA zwitterionic polymer brush layer can form a stable hydration layer on the membrane surface, effectively inhibiting the adsorption of oil and organic pollutants and improving the membrane's antifouling performance. The PDMAEMA responsive chain segment endows the membrane with good pH response performance, enabling the membrane surface wettability to be reversibly regulated with changes in ambient pH, thereby achieving on-demand separation of oil-in-water emulsions and water-in-oil emulsions.
[0057] The PVDF / CdS / MIL-125-PSADA composite membrane prepared in this invention exhibits excellent wetting and emulsion separation performance, demonstrating high separation efficiency and permeate flux for various emulsion systems, including petroleum ether, n-hexane, toluene, and 1,2-dichloroethane. Furthermore, the membrane exhibits good cycling stability and antifouling properties, maintaining high separation efficiency even after multiple cycles. In addition, under the synergistic effect of visible light and H₂O₂, the CdS / MIL-125-Br heterojunction can continuously generate ·OH and ·O₂. -The active oxygen species effectively degrade organic pollutants adsorbed on the membrane surface, achieving rapid self-cleaning and performance recovery. After multiple cycles, the membrane maintains a high flux recovery rate and stable separation performance. Therefore, the PVDF / CdS / MIL-125-PSADA composite membrane prepared in this invention achieves efficient, stable, and sustainable separation of complex oil-containing emulsion systems through the synergistic effect of pH response regulation, antifouling protection, and photocatalytic self-cleaning. This provides a new technical approach for the design of on-demand oil-water separation membrane materials and the treatment of oily wastewater, demonstrating promising application prospects and widespread value.
[0058] The composite membrane prepared in this invention forms a stable zwitterionic hydration layer on its surface, which can effectively reduce oil adsorption and pollutant deposition, and improve the membrane's hydrophilicity and antifouling performance. Simultaneously, the PDMAEMA segments endow the membrane with excellent pH response characteristics, enabling reversible switching between hydrophilic / hydrophobic and oleophilic / oleophobic properties on the membrane surface, thereby meeting the on-demand separation requirements of oil-in-water emulsions and water-in-oil emulsions. The Z-shaped heterojunction constructed from CdS / MIL-125-Br not only improves the efficiency of photogenerated electron-hole separation but also continuously generates ·OH and ·O2 under the synergistic effect of visible light and H2O2. - The invention utilizes reactive oxygen species to achieve rapid degradation and in-situ self-cleaning of organic pollutants on the membrane surface. The on-demand oil-water separation membrane prepared in this invention exhibits excellent wetting control, high separation flux, and high separation efficiency, demonstrating good separation performance for various oil-in-water emulsions such as petroleum ether, n-hexane, toluene, and 1,2-dichloroethane. It also possesses excellent cycling stability and antifouling properties, maintaining high separation efficiency and flux recovery rate even after multiple cycles. Through the synergistic effect of the zwitterionic antifouling layer, pH-responsive polymer brush layer, and CdS / MIL-125-Br photocatalytic components, efficient separation, fouling inhibition, and self-cleaning regeneration of emulsion systems are achieved, providing a new technical approach for the treatment of complex oily wastewater and the development of on-demand oil-water separation membrane materials.
[0059] The above embodiments are merely one of the implementation methods for achieving the technical solution of the present invention. The scope of protection claimed by the present invention is not limited to this embodiment, but also includes any variations, substitutions and other implementation methods that can be easily conceived by those skilled in the art within the scope of the technology disclosed in the present invention.
Claims
1. A method for preparing a photocatalytic self-cleaning oil-water separation membrane with pH-responsive characteristics, characterized in that, include: The bromine-functionalized organic ligand Br-BDC was synthesized using 2-aminoterephthalic acid, triethylamine, and α-bromoisobutyryl bromide. MIL-125-Br metal-organic framework material was prepared by reacting the brominated organic ligand Br-BDC with tetrabutyl titanate. CdS nanoparticles were loaded onto the surface of MIL-125-Br metal-organic framework material using a solvothermal method to construct a CdS / MIL-125-Br Z-type heterojunction nanocomposite material. PVDF / CdS / MIL-125-Br composite membranes were prepared by dissolving polyvinylidene fluoride, polyvinylpyrrolidone, and CdS / MIL-125-Br Z-type heterojunction nanocomposite materials in N,N-dimethylacetamide and using a non-solvent-induced phase separation method. Using atom transfer radical polymerization, zwitterionic polymer polysulfobetaine methacrylate was grafted onto the surface of a PVDF / CdS / MIL-125-Br composite membrane to obtain a PVDF / CdS / MIL-125-PSBMA superhydrophilic membrane. Using the ATRP polymerization method, pH-responsive monomers were grafted onto the surface of a PVDF / CdS / MIL-125-PSBMA superhydrophilic membrane to construct a dynamic wetting control layer, thereby obtaining a photocatalytic self-cleaning oil-water separation membrane with pH-responsive characteristics.
2. The method for preparing a photocatalytic self-cleaning oil-water separation membrane with pH-responsive characteristics according to claim 1, characterized in that, The process for synthesizing the bromine-functionalized organic ligand Br-BDC using 2-aminoterephthalic acid, triethylamine, and α-bromoisobutyryl bromide is as follows: Under nitrogen protection, 2-aminoterephthalic acid and triethylamine were dissolved in tetrahydrofuran and placed in an ice bath. Then, α-bromoisobutyryl bromide was added dropwise. After the addition was complete, the reaction was stirred at room temperature. After the reaction was completed, the by-product salt was removed by centrifugation, and the remaining solution was poured into toluene for precipitation. The precipitated solid was collected and washed with deionized water and acetone in sequence. Then it was dried under vacuum to obtain the bromine-functionalized organic ligand Br-BDC.
3. The method for preparing a photocatalytic self-cleaning oil-water separation membrane with pH-responsive characteristics according to claim 1, characterized in that, The molar ratio of 2-aminoterephthalic acid, triethylamine and α-bromoisobutyryl bromide is 1:(0.8-1.2):(0.8-1.2).
4. The method for preparing a photocatalytic self-cleaning oil-water separation membrane with pH-responsive characteristics according to claim 1, characterized in that, The process of preparing MIL-125-Br metal-organic framework material by reacting the brominated organic ligand Br-BDC with tetrabutyl titanate is as follows: Bromine-functionalized organic ligand Br-BDC and tetrabutyl titanate were added to a mixed solvent consisting of N,N-dimethylformamide and methanol. After stirring, a solvothermal reaction was carried out. After the reaction was completed and cooled to room temperature, the precipitate was collected by centrifugation, washed, and dried to obtain the MIL-125-Br metal-organic framework material.
5. The method for preparing a photocatalytic self-cleaning oil-water separation membrane with pH-responsive characteristics according to claim 1, characterized in that, The process of constructing a CdS / MIL-125-Br Z-type heterojunction nanocomposite material by loading CdS nanoparticles onto the surface of MIL-125-Br metal-organic framework material using a solvothermal method is as follows: MIL-125-Br metal-organic framework material was ultrasonically dispersed in N,N-dimethylformamide, followed by the addition of cadmium nitrate and thiourea and stirring until homogeneous for a solvothermal reaction. After the reaction was completed, the product was collected by filtration, washed, and dried to obtain CdS / MIL-125-Br Z-type heterostructure nanocomposite material.
6. The method for preparing a photocatalytic self-cleaning oil-water separation membrane with pH-responsive characteristics according to claim 1, characterized in that, The process of preparing a PVDF / CdS / MIL-125-Br composite membrane by dissolving polyvinylidene fluoride, polyvinylpyrrolidone, and CdS / MIL-125-Br Z-type heterojunction nanocomposite material in N,N-dimethylacetamide and then using a solvent-inducible phase separation method is as follows: Polyvinylidene fluoride (PVDF) and polyvinylpyrrolidone (PVP) were added to N,N-dimethylacetamide and heated and stirred until completely dissolved to obtain a homogeneous and transparent PVDF mixed solution. CdS / MIL-125-Br Z-type heterojunction nanocomposite material was ultrasonically dispersed in N,N-dimethylacetamide to obtain a CdS / MIL-125-Br nanocomposite solution. The PVDF mixed solution and the CdS / MIL-125-Br nanocomposite solution were mixed and heated and stirred to obtain a uniform casting solution. After degassing, the casting solution was uniformly coated onto the surface of a glass plate, exposed to air, and then immersed in a coagulation bath for phase inversion to obtain a PVDF / CdS / MIL-125-Br composite membrane.
7. The method for preparing a photocatalytic self-cleaning oil-water separation membrane with pH-responsive characteristics according to claim 1, characterized in that, The process of grafting the zwitterionic polymer polysulfobetaine methacrylate onto the surface of a PVDF / CdS / MIL-125-Br composite membrane using atom transfer radical polymerization to obtain a PVDF / CdS / MIL-125-PSBMA superhydrophilic membrane is as follows: The PVDF / CdS / MIL-125-Br composite membrane was immersed in a mixed solution of methanol and deionized water, and SBMA monomer, 2,2-bipyridine and CuBr were added. The ATRP polymerization reaction was carried out under nitrogen protection. After the reaction was completed, the membrane was washed and dried to obtain the PVDF / CdS / MIL-125-PSBMA superhydrophilic membrane.
8. The method for preparing a photocatalytic self-cleaning oil-water separation membrane with pH-responsive characteristics according to claim 1, characterized in that, The process of grafting pH-responsive monomers onto the surface of a PVDF / CdS / MIL-125-PSBMA superhydrophilic membrane using the ATRP polymerization method to construct a dynamically wetting control layer and obtain a photocatalytic self-cleaning oil-water separation membrane with pH-responsive characteristics is as follows: The PVDF / CdS / MIL-125-PSBMA superhydrophilic membrane was immersed in a mixed solution of methanol and deionized water, and DMAEMA monomer, Bpy and CuBr were added. The ATRP polymerization reaction was carried out under nitrogen protection. After the reaction, the membrane was washed and dried to obtain a photocatalytic self-cleaning oil-water separation membrane with pH response characteristics.
9. A photocatalytic self-cleaning oil-water separation membrane with pH-responsive characteristics, characterized in that, The photocatalytic self-cleaning oil-water separation membrane with pH response characteristics was prepared using the preparation method described in any one of claims 1-8. Among them, under acidic conditions, the photocatalytic self-cleaning oil-water separation membrane with pH response characteristics exhibits superhydrophilic / underwater superoleophobic properties. Under neutral or alkaline conditions, the photocatalytic self-cleaning oil-water separation membrane with pH response characteristics exhibits hydrophobic / oleophilic properties. Under the synergistic effect of visible light and H2O2, the photocatalytic self-cleaning oil-water separation membrane with pH response characteristics can degrade methylene blue, thereby achieving photocatalytic self-cleaning of the membrane material.
10. The application of the photocatalytic self-cleaning oil-water separation membrane with pH-responsive characteristics as described in claim 9, characterized in that, The photocatalytic self-cleaning oil-water separation membrane with pH response characteristics is used for oil-water separation treatment of emulsified oily wastewater, complex oil-water systems, or industrial oily waste liquid.
